Relationship between coronary microvascular dysfunction (CMD) and left ventricular diastolic function in patients with symptoms of myocardial ischemia with non-obstructive coronary artery disease (INOCA) by cardiovascular magnetic resonance feature-tracking - Kong, H.; Cao, J.; Tian, J.; Yong, J.; An, J.; Song, X.; He, Y. (Clinical radiology, 2024)
To investigate whether there was an association between coronary microvascular dysfunction (CMD) and left ventricular (LV) diastolic function in patients with myocardial ischemia with non-obstructive coronary artery disease (INOCA). Our study included 115 subjects with suspected myocardial ischemia that underwent stress perfusion cardiac magnetic resonance (CMR). They were divided into non-CMD and CMD two groups. CMR-derived volume-time curves and CMR-FT parameters were used to assess LV diastolic function using CVI42 software. The latter included global/regional LV peak longitudinal, circumferential, radial diastolic strain rate (LDSR, CDSR, RDSR). Logistic regression analysis was performed with CMR-FT strain parameters as independent variables and CMD as dependent variables, and the effect value was expressed as an odds ratio (OR). Of the 115 patients, we excluded data from 23 patients and 92 patients (56.5% male；52 ± 12 years) were finally included in the study. Of these, 19 patients were included in the non-CMD group (49 ± 11 years) and CMD group included 73patient (52 ± 12 years). The regional CDSR (P=0.019), and regional RDSR (P=0.006) were significantly lower in the CMD group than in non-CMD group. But, regional LDSR in CMD group was higher than non-CMD (P=0.003). In logistic regression analysis, regional LDSR (adjusted β= 0.1, 95%CI 0.077, 0.349, p=0.002) and RDSR (adjusted β= 0.1, 95 % CI 0.066, 0.356, p=0.004) were related to CMD. LV myocardial perfusion parameter MPRI was negatively correlated with LV diastolic function (CDSR) which needs to take into account the degree of diastolic dysfunction. •LV global diastolic function did not decrease in CMD patients.•The myocardial segments with CMD had diastolic dysfunction.•MPRI was associated with LV diastolic function in INOCA patients.